Comparing the Effectiveness of Solution-Focused Narrative Therapy and Solution-Focused Therapy on Resilience and Marital Intimacy of Couples in Conflict (Counseling Centers of Shirvan County) - Faraydoni Golyan , Goldasteh; Sadeghifard , Maryam; Yosefi , Emad (Health Nexus, 2025)
The present study aimed to compare the effects of solution-focused narrative therapy and solution-focused therapy on resilience and marital intimacy among couples in conflict. This research employed a quasi-experimental design with a pre-test, post-test, and control group, along with a two-month follow-up. The statistical population consisted of all couples experiencing marital conflict who referred to counseling centers in Shirvan County during 2022-2023. The study sample included 30 couples (20 participants in each group) with marital conflict who were selected using convenience sampling from clinics and counseling centers in Shirvan County and randomly assigned to two experimental and one control group. Solution-Focused Narrative Therapy (SFNT) and Solution-Focused Therapy (SFT) were administered separately over six sessions for the experimental groups, while the control group received no intervention. Data collection instruments included the Bagarozi Marital Intimacy Questionnaire (2001) and the Connor-Davidson Resilience Scale (2003). Collected data were analyzed using repeated measures analysis of variance and Bonferroni post hoc tests, with SPSS-26 software. Results indicated that both solution-focused narrative therapy and solution-focused therapy were effective in improving resilience and marital intimacy among couples in conflict (p < .001). Additionally, Bonferroni test results revealed that the therapeutic effects of both approaches on resilience and marital intimacy were maintained after two months (p < .001). Moreover, findings demonstrated that solution-focused narrative therapy had a greater impact on resilience and marital intimacy compared to solution-focused therapy (p < .001). Based on these results, both approaches can be used to resolve marital conflict, although solution-focused narrative therapy showed greater effectiveness than solution-focused therapy.